The Impact of p53 and Ki67 Expression in Endometrial Cancer and its Effect on Survival - Zekiye Sahin; Burak Bayraktar; Tugba Karadeniz; Muzaffer Sanci (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: This study was conducted to evaluate the relationship of p53 and Ki67 expression with prognostic factors in patients who underwent surgery due to a diagnosis of endometrial cancer, and to evaluate their use as molecular markers that can help with survival prediction.